2013
DOI: 10.5694/mja12.11849
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of influenza vaccine by pregnant women: a cross‐sectional survey

Abstract: Recommendation from a health care provider is strongly associated with influenza vaccine uptake among pregnant women and can overcome their concerns about safety, but less than half the women surveyed reported receiving such a recommendation. Educational material targeting pregnant women and professional education and support for antenatal health care providers are needed to increase awareness and recommendation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
122
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 19 publications
9
122
0
1
Order By: Relevance
“…18,34 Thus rather than being a problem requiring change in HCP or maternal attitudes and knowledge, efforts to improve uptake could usefully focus on including these vaccines in routine care. Our study and others 15,22,23 suggest that many women would accept these immunizations if offered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…18,34 Thus rather than being a problem requiring change in HCP or maternal attitudes and knowledge, efforts to improve uptake could usefully focus on including these vaccines in routine care. Our study and others 15,22,23 suggest that many women would accept these immunizations if offered.…”
Section: Discussionmentioning
confidence: 99%
“…As with parental decision-making in childhood vaccination decisions, 25 HCP endorsement appears to be a key factor in the decision making process for pregnant mothers about vaccines during pregnancy. 22,23,30,33 Midwives, obstetricians and GPs play a vital role not only in raising awareness about recommended vaccines, but also in raising awareness about the importance of being protected against influenza as a pregnant mother and similarly the importance of protecting their baby against pertussis and influenza at a time related to high mortality. We found that the women in our study were not generally aware that pregnancy increases their risk of acquiring vaccine-preventable infections and that some of those who were hesitant to accept vaccination cited their low risk of infection as the reason.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of parental position on immunisation, trust in health professionals and services is paramount. 63,65 Studies have also explored factors influencing uptake of immunisation in adults 66,67 including those with high-risk conditions, 68 pregnant women 69,70 and minority ethnic groups. 71 The barriers appear to broadly fall into the same two categories, access and beliefs, including the perception that healthy people do not need immunisations.…”
Section: Factors Influencing the Uptake Of Immunisationmentioning
confidence: 99%